2017
DOI: 10.17781/p002314
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Performance of Three Machine Learning Algorithms for Tweets on Nigerian dataset

Abstract: The popularity of Twitter as a social media platform is increasingly becoming very important, this has no doubt impact positively on the business, social and political aspect of our lives, and hence, the need for researchers to focus on Twitter opinion miming became crucial. Despite the increase in the number of Twitter users in Nigeria generating a huge amount of data from the discussions on national issues became a challenge; limited research has been carried out on Twitter data sources from Nigerian context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Various data mining methods have been used by different researchers for estimating preferable algorithms (Mythili and Mohamed, 2014;Nikolovski et al,, 2015). In general Data mining processes follows a set of steps that must be executed regardless of the algorithms or methodology that will be implemented (Tabra and Lawan, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Various data mining methods have been used by different researchers for estimating preferable algorithms (Mythili and Mohamed, 2014;Nikolovski et al,, 2015). In general Data mining processes follows a set of steps that must be executed regardless of the algorithms or methodology that will be implemented (Tabra and Lawan, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…A cross validation test result [5] indicates that data mining techniques predicted significantly better than its statistical counterpart. Therefore, [6] suggested that with the increasing need for data mining and analyses, there is a need for improving the performance of data mining models and machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%